The Body and Desire: Gregory of Nyssa's Ascetical Theology. By Raphael A. Cadenhead. Christianity in Late Antiquity. Oakland: University of California Press, 2018. xii + 267 pp. $95.00 cloth. - Radde-Gallwitz, Andrew (Church history, 2021)
//static.cambridge.org/content/id/urn%3Acambridge.org%3Aid%3Aarticle%3AS000964072100086X/resource/name/firstPage-S000964072100086Xa.jpg